'Rooted mobilities' in young people's narratives of the future: A peripheral case. (November 2018) - Cuzzocrea, Valentina
Youth research recognises that the struggles typical of the transition to adulthood can no longer be assumed to occur 'at home'. However, few investigations have focused on how the imagination of mobility shapes that which is not home yet but which may later become so. To address this lacuna, this article engages with how the imagination of the future of young people is entrenched with 'motility', namely, the possibility for a type of movement that arises out of a specific relationship with one's current context. Focusing on Sardinian youth, the article problematises the strong mobility orientation which can occur through the unfolding of an imagined continuous 'lived' relationship with Sardinia. The author calls this 'rooted mobility'. The article discusses the limits that accompany such mobility, and the potential for social action that emerges, framing narratives of the future within the conditions of peripherality in which young Sardinians live. The article draws on 341 essays on the topic of the future collected from students in their penultimate year of school.